NON-HUMANS AS MEANING-MAKERS: ELIZABETH AS A CO- DESIGNER of BIOSHOCK INFINITE - Malazita, James W. (AoIR Selected Papers of Internet Research, 2015)
Who participates in the Community of Practiceof the design of digital technology? Cultural studies scholars traditionally focus on human elements as the key actants and meaning-makers in the design of technology. Even Actor-Network Theory, which attributes causal power to non-human material objects, stops short of crediting objects with interpretive power and meaning-making ability. However, recent theoretical approaches coming out of Speculative Realism, New Materialism, and Non-Human Ethnography are posing challenges to this anthropocentric model of meaning-making.